Clinical Experience with the Use of a Handheld Doppler in the Detection of Cutaneous Perforators and its Application and Reliability in Pre-Operative Planning of Perforator Based Flaps (Medical Forum Monthly, 2024)
Objective: To determine the accuracy & reliability of handheld Doppler in preoperative planning of a perforator based flap.Study Design: Descriptive case series study.Place and Duration of Study: This study was conducted at the Department of Orthopaedics and Plastic Surgery, Multan Medical & Dental College/ Ibne Siena Hospital& Research Institute, Multan from July 2018 to Jan 2019.Materials and Methods: A total of 25 patients with skin & soft tissue defects were included in the study. A handheld Life Dop Doppler with an 8 MHz probe was used to detect the cutaneous perforators pre-operatively while planning a perforator based flap and its results were correlated with intra-operative actual perforator location.Results: A total of 71 perforators were marked for perforator based flaps in 25 patients, 55 in lower limbs, and 16 in upper limbs. Out of 55 lower limb perforators, 47 were correct, 3 were false positive & 5 were false negative. Out of 16 upper limb perforators, 13 were correct, 1 was false positive & 2 were false negative.Conclusion: Despite of the limitations associated with handheld Doppler, in selective patients, it is still a simple & reliable option in the planning of perforator based flaps for skin & soft tissue reconstructions.